Alfabetização de idosos e adultos ou leitura e escrita? - Maria Hermínia Lage Fernandes Laffin (Universidade do Minho, 2012)
This paper presents an analysis of elderly and adults' literacy education at Núcleo de Estudos da Terceira Idade/UFSC (Elderly People Study Research Group/UFSC), between 2007 and 2010, undertaken in partnership with Florianopolis County Education Department. I discuss the right of elderly people and adults to competent professionals in schooling, appropriate study conditions and didactic materials, as well as adequate structural facilities. Starting with a study on the sociological and anthropological aspects of the educational processes at school, in this text I analyze some elements of the literacy course, and I also inquire people involved in it. As theoretical contributions that were fundamental to this study I must highlight the works of Charlot (2000), Louro (1997), Menezes (2005), Soares (2000), Paiva (1997) and Sartori (2010). As main results I stress a set of elements marked by gender categories, generation issues and the economic needs of a group of people searching for space and the right to social inclusion.